Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9tc02849h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a hybrid ferroelectric with a 1-D perovskite-like structure: bis(pyrrolidinium) pentachloroantimonate(iii)

Abstract: Herein, a multi-phase ferroelectric and ferroelastic pyrrolidinium-based organic–inorganic hybrid (C4H8NH2)2[SbCl5] is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
2
28
0
1
Order By: Relevance
“…The LT phases of pyrrolidinium-based organic–inorganic hybrids often possess ferroelectric or even multiferroic properties. 27 , 28…”
Section: Resultsmentioning
confidence: 99%
“…The LT phases of pyrrolidinium-based organic–inorganic hybrids often possess ferroelectric or even multiferroic properties. 27 , 28…”
Section: Resultsmentioning
confidence: 99%
“…• one-dimensional (1D) chains (cis-or trans-type) (Fig. 4(a) and (b) respectively) [100][101][102][103][104][105][106][107][108][109] • isolated [M 2 X 10 ] 4− units (two edge-sharing octahedra) (Fig. 4(c)); 49,110,111 Fig.…”
Section: Rmx 4 (R : M = 1 : 1)mentioning
confidence: 99%
“…[MX 5 ] N chain. [36][37][38][39][40][41][42][43][44][45] While (i)-(iv) ferroelectric cases are well known by now, particularly interesting is the recent signicant boost in the number of reported ferroelectric materials with [MX 5 ] N chains (v).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 1D units, chains of trans-connected MX 6 3À octahedra ($180 X bridging -M-X bridging angle) and cis-connected MX 6 3À octahedra ($90 X bridging -M-X bridging angle) can be distinguished. In 2012, 46 we performed a structural survey, recently updated by Ksiądzyna et al, 44 of R 2 MX 5 compounds deposited in the Cambridge Structural Database to nd a relationship between the acentric symmetry of the compounds and the type of anionic unit present in a crystal. The results of the survey indicated that innite 1D chains lead more frequently to the acentric arrangement (40% of cases) than 0D units (up to 10% of cases).…”
Section: Introductionmentioning
confidence: 99%